2009
DOI: 10.1111/j.1524-4725.2009.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience in the Treatment of Different Vascular Lesions Using a Neodymium-Doped Yttrium Aluminum Garnet Laser

Abstract: A variable long-pulsed Nd:YAG laser was found to be effective in the treatment of different vascular lesions ranging from easy to difficult to treat. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 17 publications
1
36
0
5
Order By: Relevance
“…Heutzutage werden Naevi flammei z. B. mit Laser, photodynamischer Therapie, Kryothera- [1,2,4,5,6,7,8,11,16,18,22,23,25,26].…”
Section: Diskussionunclassified
“…Heutzutage werden Naevi flammei z. B. mit Laser, photodynamischer Therapie, Kryothera- [1,2,4,5,6,7,8,11,16,18,22,23,25,26].…”
Section: Diskussionunclassified
“…1c) 1,5,11,12,20,27,32,34,41,53,56–58,70,71,79,80,83,84,88,90,109,110,113,124,130,133,144,159,160. This overview therefore focuses on the causes of the therapeutic recalcitrance and presents several experimental engineering approaches, including (1) alterations in local hemodynamics, (2) concomitant laser treatment and dermo-vascular imaging, and (3) site-specific pharmaco-laser therapy, with which the therapeutic efficacy of recalcitrant PWSs may be improved.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the results of evaluation of other commonly used treatment methods for viral warts in the previous report, the results of our study indicate that LP-Nd:YAG is a safe and effective modality for the treatment of refractory warts, while causing minimal discomfort. 16 Though Han et al 16 reported extremely higher clearance rate for treating common warts (96%) but they had inevitable adverse effects under the protocol with longer duration previous papers 19 have described that the protocol with shorter duration (15 msec) and lower fluence (150-185 J/cm 2 ) are enough for desiccating the vessels for telangiectasia and spider angiomas and accomplished higher clearance rate with no remarkable side-effect. Therefore, we have decided that our protocol for treating the recalcitrant warts with a duration of approximately 15 msec and fluence of approximately 150-185 J/cm 2 is sufficient to damage the vasa vasorum of recalcitrant warts.…”
Section: Discussionmentioning
confidence: 99%